1997
DOI: 10.1016/s0377-1237(17)30638-x
|View full text |Cite
|
Sign up to set email alerts
|

Tensor Fascia Lata/Gluteus Medius Muscle Pedicle Bone Graft for Non-Union of Femoral Neck Fractures

Abstract: Twelve male patients with non-union of fracture neck femur of 6-12 months duration were managed by open reduction and internal fixation and tensor fascia lata or gluteus medius muscle pedicle bone grafting through the anterior route. Internal fixation was done with Knowles pins and Asinis screws or combination of both. !1nion could be achieved in II out ofthe 12 cases. Functional recovery of hip was good in 9, fair in 2 and poor In one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The effective rate was reported by 10 studies involving 612 patients; of these, three used self-established criteria [ 27 – 29 ], four used the modified Harris hip score [ 16 , 18 , 21 , 25 ], one used the Salvati and Wilson score [ 20 ], one study used the Sanders score [ 22 ], and one study used the modified Postel and Merle d’Aubigne hip scoring to assess the effective rate [ 19 ]. An average effective rate of 73.4% were considered good, while rates of 15.4% and 10.9% were considered fair and poor, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective rate was reported by 10 studies involving 612 patients; of these, three used self-established criteria [ 27 – 29 ], four used the modified Harris hip score [ 16 , 18 , 21 , 25 ], one used the Salvati and Wilson score [ 20 ], one study used the Sanders score [ 22 ], and one study used the modified Postel and Merle d’Aubigne hip scoring to assess the effective rate [ 19 ]. An average effective rate of 73.4% were considered good, while rates of 15.4% and 10.9% were considered fair and poor, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, half of these studies had fewer than 20 patients, and the individual differences in rates were large. For example, Hou et al reported a collapse rate of 0.00% in 5 patients, whereas Morwessel et al reported a collapse rate of 23.08% in 13 patients [ 29 , 34 ]. Furthermore, most of the studies did not report the details pertaining to the diagnosis of the collapse and nonunion rates; thus, the consistency in these rates across the included studies could not be guaranteed.…”
Section: Discussionmentioning
confidence: 99%